2019
DOI: 10.1186/s13046-019-1220-1
|View full text |Cite
|
Sign up to set email alerts
|

DEPTOR induces a partial epithelial-to-mesenchymal transition and metastasis via autocrine TGFβ1 signaling and is associated with poor prognosis in hepatocellular carcinoma

Abstract: Background DEPTOR is an endogenous inhibitor of mTORC1 and mTORC2 that plays a vital role in the progression of human malignances. However, the biological function of DEPTOR in HCC metastasis and the underlying molecular mechanisms are still unclear. Methods Western blot analysis and immunohistochemistry(IHC) were employed to examine DEPTOR expression in HCC cell lines and tissues. A series of in vivo and in vitro assays were performed to determine the function of DEPTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Overexpression of DEPTOR promotes proliferation and survival of cancer cells. DEPTOR induces a partial E-to-M transition and metastasis via autocrine TGF-β1 signaling in HCC [27]. Endosulfan is an organochlorine pesticide that is mainly metabolised by cytochrome P450 (CYP) enzymes, CYT2B6 and CYT3A4, in human liver.…”
Section: Miscellaneous Regulatorsmentioning
confidence: 99%
“…Overexpression of DEPTOR promotes proliferation and survival of cancer cells. DEPTOR induces a partial E-to-M transition and metastasis via autocrine TGF-β1 signaling in HCC [27]. Endosulfan is an organochlorine pesticide that is mainly metabolised by cytochrome P450 (CYP) enzymes, CYT2B6 and CYT3A4, in human liver.…”
Section: Miscellaneous Regulatorsmentioning
confidence: 99%
“…Unraveling inter-pathway regulation in EMT and deciphering what signaling pathways are required for different stages/steps of EMT (e.g., initiation, progression, maintenance, the cadherin switch, loss of cell polarity and other phenotypic alterations) is of vital importance. Recently, the DEPTOR (DEP domain containing mTOR interacting) protein which normally inhibits mTOR signaling, stimulated partial EMT in HCC cells by activating TGFβ-Smad3/4-Snail signaling through mTOR inhibition (88). Similarly, in vitro mimicking of ECM organization showed that the way the ECM is arranged could trigger partial or full EMT (89).…”
Section: In Tune With Emt Intracellular Signalingmentioning
confidence: 99%
“…Lastly, overexpression of DEPTOR, an mTOR-interacting protein, whose expression is negatively regulated by mTORC1 and mTORC2, promoted the invasion and metastasis of HCC cells in vitro and in vivo. DEPTOR induced an EMT and metastasis via up-regulation of Snail, which was due, in turn, to activation of aTGF-β1-Smad3/4 signaling, possibly through feedback inhibition of mTOR [ 82 ].…”
Section: Autocrine Tgf-β In the Regulation Of Specific Proteinsmentioning
confidence: 99%